An Unsteady Heterogeneous Mass Transfer Model for Gas Absorption Enhanced by Dispersed Third Phase Droplets - 沈树华 马友光 卢素敏 朱春英 (Chinese journal of chemical engineering, 2009)
A model for one-dimensional unsteady heterogeneous mass transfer was developed based on Danck- werts＇ surface renewal theory in order to describe the mass transfer enhancement of absorption process for a slightly soluble gas in a gas-liquid-liquid system. The model accounts for the mass transfer resistance within the dispersed phase and the effect of emulsion viscosity on mass transfer. An analytical solution for enhancement factor was obtained by Laplace domain transformation. The absorption rates of carbon dioxide in the dodecane-in-water and castor oil-in-water systems were measured in a thermostatic reactor, and the enhancement factors were calculated at different volume fractions of dispersed phase and stirrer speeds. The model predictions agree well with the experimental data.